Aquasaver band: scuba emergency bracelet - Ashan, Mohd Zulfahmi; Francis, Debra Utih; Dominic, Floria Ann; Pilem, Stephanie; Fatt, Boyd Sun (Universiti Teknologi MARA, Kedah, 2023)
Scuba diving is considered to be one of the most challenging and high-risk activities or hobbies. This activity can only be performed after completing a course and receiving proper training. There have been numerous fatalities associated with scuba diving. This situation arises due to the absence of safety measures for engaging in this activity. Consequently, we took the initiative to introduce a tool that will enhance the safety of this extreme activity. The name of this tool is the AquaSaver Band. The AquaSaver Band is a bracelet designed for emergency situations during scuba diving activities. The emergency bracelet is designed to provide safety protocols and security features for divers, particularly those who are new to diving, in case of any unforeseen danger or emergency situations that may arise while they are in the middle of the sea. Among the AquaSaver Band features are the detection of an emergency for people wearing the and those around them, facilitates dive operators in monitoring divers who wear it, can assist divers and minimize the likelihood of accidents during diving. The AquaSaver Band is not just useful for emergencies, but also helps divers prepare before and during their dives which effectively handle any emergencies that may arise for themselves or other divers. Ultimately, wearing the AquaSaver Band can enhance the safety of the diver.